Wizja wieku siedemnastego według trzech autorów powieści historycznych: Henryka Sienkiewicza, Józefa Hena i Jacka Komudy = The vision of the 17th century according to three writers of historical novels: Henryk Sienkiewicz, Józef Hen and Jacek Komuda - Mróz, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is an attempt to answer a question in what way three different authors of his?torical novels (Sienkiewicz, Hen, Komuda) perceived the 17th century in the Polish history and how they described it in their works.
Keywords: powieść historyczna; historia; wojna; kobiecość; miłość; historical novel; war; history; love; femininity